Rapid and Stable Formation Method of Human Astrocyte Spheroid in a High Viscous Methylcellulose Medium and Its Functional Advantages - Fumiya Tao; Keita Kitamura; Sanshiro Hanada; Kazuyuki Sugimoto; Tomomi Furihata; Nobuhiko Kojima (Bioengineering, 2023)
Astrocytes, a type of glial cell in the brain, are thought to be functionally and morphologically diverse cells that regulate brain homeostasis. Cell immortalization is a promising technique for the propagation of primary human astrocytes. The immortalized cells retain their astrocytic marker mRNA expression at lower levels than the primary cells. Therefore, improvement of the differentiation status is required. The use of a 3D formation technique to mimic structural tissue is a good strategy for reflecting physiological cell–cell interactions. Previously, we developed a spheroid formation method using highly viscous methyl cellulose (MC) medium. In this study, we applied this formation method to the well-established immortalized human astrocyte cell line HASTR/ci35. Stable HASTR/ci35 spheroids were successfully formed in MC medium, and laminin deposition was detected inside of the spheroids. Their functional markers were enhanced compared to conventional spheroids formed in U-bottom plates. The inflammatory response was moderately sensitive, and the ability to support neurite growth was confirmed. The HASTR/ci35 spheroid in the MC medium demonstrated the differentiation phenotype and could serve as a potent in vitro model for matured astrocytes.